1999
DOI: 10.1115/1.555390
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Flow Fields Predicted by Various Turbulent Lubrication Models With Existing Measurements

Abstract: Flow field predictions of various turbulent lubrication models are compared with the existing experimental data of turbulent Couette flow and shear-induced countercurrent flow. [S0742-4787(00)00502-6]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…where h 0 is minimum oil film thickness, h p is microtexture depth, w is circumferential coordinate, r is radial coordinate, p is fluid pressure, m is the dynamic viscosity of lubricating fluid and v is the thrust bearing rotational speed. Modern machinery is evolving toward higher rotational speeds and greater power; it has been demonstrated that many largescale bearings have already operated in turbulent flow conditions (Wang et al, 2000). The motion characteristics of viscous fluids differ significantly between laminar and turbulent flow states.…”
Section: The Theoretical Model Of Numerical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…where h 0 is minimum oil film thickness, h p is microtexture depth, w is circumferential coordinate, r is radial coordinate, p is fluid pressure, m is the dynamic viscosity of lubricating fluid and v is the thrust bearing rotational speed. Modern machinery is evolving toward higher rotational speeds and greater power; it has been demonstrated that many largescale bearings have already operated in turbulent flow conditions (Wang et al, 2000). The motion characteristics of viscous fluids differ significantly between laminar and turbulent flow states.…”
Section: The Theoretical Model Of Numerical Calculationmentioning
confidence: 99%
“…Modern machinery is evolving toward higher rotational speeds and greater power; it has been demonstrated that many large-scale bearings have already operated in turbulent flow conditions (Wang et al , 2000). The motion characteristics of viscous fluids differ significantly between laminar and turbulent flow states.…”
Section: The Theoretical Model Of Numerical Calculationmentioning
confidence: 99%
“…kx, kz turbulence factor is a function of the local Reynolds number from the wall's law [10] obtained the following formula 0.9 0.98 12 0.0136(Re) 12 0.0043(Re)…”
Section: Fig1 Failure Bearing Picturesmentioning
confidence: 99%
“…Numerous researchers have studied turbulent lubrication, and various models have been proposed, including the Ng–Pan model (Ng, 1964; Ng and Pan, 1965), bulk flow model (Hirs, 1970; Hirs, 1973), Constantinescu model (Constantinescu, 1962) and Elrod–Ng model (Elrod and Ng, 1967). Wang et al. (2000) evaluated the accuracy of the turbulence model mentioned above and pointed out that the Ng–Pan model has a wider range of applicability.…”
Section: Introductionmentioning
confidence: 99%